A new species of Asthenopus (Ephemeroptera: Polymitarcyidae: Asthenopodinae) from Brazil and Colombia - Molineri, Carlos; Cruz, Paulo Vilela; Emmerich, Daniel (Zootaxa, 2011)
A new species of Asthenopus, A. crenulatus sp. nov. is described from adults of both sexes from Brazil and Colombia. The new species is diagnosed by: male foreleg length 0.7–0.9 times the length of fore wing, marginal intercalary veins on the entire margin of fore and hind wings generally shorter than distance between longitudinal veins, forceps and penes long and slender, penes with many subapical spines. This new species is closely related with A. picteti (Hubbard). A key to the male adults of Asthenopus is included.